Cryptocurrency Transaction: is it Relevant to Indonesian Accounting Standards? - Rahmi Nadiar; Wahyudin Nor; Lili Safrida (Universitas Muhammadiyah Surakarta, 2022)
Background: There are no specific accounting standards that may relevant to cryptocurrency transactions. This leads to different accounting treatments for many entities. Based on the existing issues and regulations in Indonesia, how is the classification of accounts that possibly relevant to the Indonesian accounting standard?Purpose and Methods: This study seeks to explain and analyse the accounting challenges for cryptocurrencies within the current accounting framework in Indonesia. As well as to identify relevant models for cryptocurrency accounting. This study is qualitative. Data sources used in this study include key informant interviews.Findings: The study findings concluded that tere are deficiencies in the Indonesian accounting standard. This is driven by differences in the use of an entity’s business model. Differences in business activity leads to differing uses in cryptocurrency accounting.Research Limitation: The results of the research depend on the author’s experience and perspective. The scope of topics can be broadened by adding additional perspectives.Contribution: Contribute to developing the accounting standards in Indonesia. The growing popularity of cryptocurrencies has indirectly led the regulators to create new guidance for accounting financial statements. Keyword: Accounting Standard, Cryptocurrency, Blockchain, Intangible Asset.